EEG with extreme delta brush in young female with methotrexate neurotoxicity supports NMDA receptor involvement. (September 2017) - Schmidt, Lisbeth Samsø; Kjær, Troels W.; Schmiegelow, Kjeld; Born, Alfred Peter
Abstract: Sub-acute neurotoxicity is a well-known complication to high-dose and intrathecal methotrexate (MTX) treatment of children with leukemia. Symptoms can be treated safely by dextromethorphan, a non-competitive antagonist to N-methyl-D-aspartic acid receptor (NMDAR). In a female with subacute MTX neurotoxicity, we observed an electroencephalographic (EEG) with extreme delta brush. Extreme delta brush is an EEG pattern previously described in patients with NMDAR autoimmune encephalitis. The observations suggest that the mechanism of this neurotoxicity may be mediated by the NMDAR. Furthermore, extreme EEG delta brush should suggest a diagnosis of MTX associated subacute neurotoxicity. Highlights: EEG with extreme delta brush can be present not only in NMDA receptor encephalitis, but also in other types of NMDA receptor pathology. EEG with extreme delta brush in patients with neurotoxicity during methotrexate therapy could have diagnostic value. Dextromethorphan, a non-competitive antagonist to NMDA-receptor is a potential effective treatment in methotrexate induced neurotoxicity.